IMPLEMANTATION OF GOVERNMENT CREDIT CARD IN REGIONAL WORK UNITS IN WONOSOBO REGENCY - Dewi Sri Lestari; Mahmudah Nufidatul (STIESA Press, 2025)
The implementation of the Government Credit Card (GCC) is part of the reform in state financial management aimed at enhancing transparency, accountability, and efficiency in budget execution through non-cash transactions. The government encourages the acceleration of financial transaction digitalization at the regional level; however, not all regional governments, including Wonosobo Regency, have implemented the GCC optimally. This study aims to examine the implementation of the GCC in Regional Work Units (SKPD) in Wonosobo Regency and to identify the challenges faced. The method used is a qualitative approach with a narrative research type. Research data were obtained through observation and interviews. The results of the study show that although there is a commitment from the Wonosobo Regency Government through regulations and pilot implementations, the execution of the GCC is still not running optimally. Four main challenges were identified: limited human resource (HR) competencies, inadequate supporting facilities, suboptimal readiness of information technology systems, and a lack of QRIS merchants. To overcome these obstacles, the suggested solutions include enhancing HR capacity, strengthening information technology infrastructure, cooperating with banks and digital payment providers, and encouraging local businesses to become QRIS merchants. These findings highlight that the success of GCC implementation is not solely determined by formal policy but also by technical readiness, the competence of government personnel, and a supportive digital ecosystem.